Edward R. Murrow waving, in front of an airplane (Tufts Archival Research Center, 2005)
7-3/8 x 9-1/2. Photo Album, souvenir from Mary Maxwell, Bob Maxwell, Bill Wilson, Bill Maxwell. Attached note indicates images may be from International Harvester.